Chenopodium quinoa Willd. (quinoa) grains: A good source of phenolic compounds. (November 2020) - Pereira, Eliana; Cadavez, Vasco; Barros, Lillian; Encina-Zelada, Christian; Stojković, Dejan; Sokovic, Marina; Calhelha, Ricardo C.; Gonzales-Barron, Ursula; Ferreira, Isabel C.F.R.
Graphical abstract: Highlights: Phenolic composition of black, red and white quinoa grains was evaluated. Quercetin and kaempferol derivatives were present in all quinoa varieties. None of the quinoa varieties showed toxicity in hepatotoxocity assay. All hydroethanolic extracts possessed antibacterial and antifungal activity. Abstract: The ingestion of bioactive compounds has revealed health benefits, namely in the prevention and/or treatment of several diseases. This work aims to characterize the phenolic profile of three colour varieties of Chenopodium quinoa Willd. grains (black, red and white), and also evaluate their cytotoxic and antimicrobial activity. All varieties revealed the presence of phenolic compounds, namely, quercetin and kaempferol derivatives. In this study, quinoa grains did not reveal any anti-proliferative capacity in tumour cell lines, and, as expected, they were devoid of any toxicity. All of the analysed extracts possessed antibacterial and antifungal activities (inhibitory and bactericidal/fungicidal) against the microbial strains considered, exhibiting promising values of minimum bactericidal concentrations (mean MBC 0.153–0.916 mg/mL) and minimum fungicidal concentrations (mean MFC 0.211–0.884 mg/mL). Quinoa varieties represent a good source of bioactive compounds, interfering beneficially in the organism, specifically as antimicrobial agents. Thus, these extracts could be used in the development of bioactive ingredients.